Restraint and Critical Incident Reduction Following Introduction of the Neurosequential Model of Therapeutics (NMT). Issue 1 (2nd January 2018) - Hambrick, Erin P.; Brawner, Thomas W.; Perry, Bruce D.; Wang, Emily Y.; Griffin, Gene; DeMarco, Toni; Capparelli, Cara; Grove, Tim; Maikoetter, Michelle; O'Malley, Dawn; Paxton, Dave; Freedle, Lorraine; et al.
ABSTRACT: Children with developmental trauma are at risk for severe and complex behavioral problems, often requiring long-term residential and day treatment. The Neurosequential Model of Therapeutics (NMT) is a developmentally sensitive approach to clinical work with a capacity-building component focusing on attachment, the impact of maltreatment and trauma, and emerging concepts in developmental psychology, neuroscience and traumatology. Research has demonstrated its effectiveness with trauma-exposed populations. NMT training may help providers working with trauma-exposed youth prevent critical incidents and reduce restraints. Restraint and critical incident data were obtained from 10 organizations providing residential and/or day-treatment services following exposure to, or certification in, the NMT. Data from the Pre-NMT Introduction period through to the Maintenance phase of NMT Certification were used to examine changes in restraints and critical incidents across phases of NMT exposure/certification. Multilevel logistic regression models suggested that NMT exposure and/or certification was associated with significant reductions in restraints and critical incidents. Reductions were sustained throughout the Maintenance phase. Estimates of potential staff hour and financial savings associated with these reductions are discussed. Implementation of the NMT in residential and day-treatment settings may result in staff, behavioral health provider, and organization-level changes that reduce critical incidents and restraint use.